THE DYNAMICS OF AGENT-STRUCTURE IN RITUAL COMMUNICATION OF THE SACRED GRAVE PILGRIMAGE - Dharma, Ferry Adhi; Dayanti, Liestianingsih Dwi; Koesbardiati, Toetik; Daud, Normadiah (al-Balagh : Jurnal Dakwah dan Komunikasi, 2024)
This study aims to explore the agent-structure relationship in ritual communication of sacred grave pilgrimage in Dewi Sekardadu at Sidoarjo. The multi-site ethnographic research method compares ritual communications and folklore at all Dewi Sekardadu’s sacred graves that spread across four cities involving Sidoarjo, Gresik, Lamongan, and Banyuwangi. The key informants were doorkeepers, grave caretakers, community leaders, pilgrims, and businessmen. The data was collected through direct observation, participant observation, in-depth interviews, and documentation. Data analysis uses Anthony Gidden’s structuration theory, referring to how the dynamic agent-structure is elaborated with the cultural meaning through the study of ritual communication. This finding implicates the development Gidden’s structuration theory for studying cultural and ritual communication in fishermen’s communities. First, the competent agent in Kepetingan succeeded changing the stigma of Kepetingan from a criminal area to a religious area through developing folklore and Nyadran ritual communication practice and grave pilgrimages. The ruler of the ritual communication arena has significance and dominance in changing the rule of ritual from spiritual practice into Islam. Second, Giddens doesn’t assume the existence of clustering of agents in society, so he couldn’t predict the way of sociocultural development of the fishermen’s community. Third, the Nyadran ritual communication structure became an identity for indigenous fishermen, which created the society structure for the grave pilgrimage in Kepetingan by the urban fishermen from Gresik and Lamongan with the identity of cultural-Islamic ritual communication.